Analisis Semiotika John Fiske Mengenai Strata Sosial pada Film The Penthouse: War In Life Season 1 - Sri Astika Yogi Pratiwi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research is entitled John Fiske's Semiotic Analysis of Social Strata in the Film The Penthouse: WarIn Life season 1. The aim of this research is to find out how the semiotic analysis of social strata is represented in the film The Penthouse; War In Life Season 1. The object of research is the film The Penthouse: War In Life Season 1. The film The Penthouse: War In Life is a Korean drama film with a screenplay by Kim Soon Ok and directed by Joo Dong Min and Park Bo Ram which was produced by Chorokbaem Media Studio S (SBS). This film is a drama film with a duration of 1 hour 19 minutes which was broadcast on October 27 2020. The method used in this research is a qualitative method using John Fiske's semiotic analysis technique. The research results show that the social strata in the film The Penthouse: War In Life season 1 mostly lead to Achieved Status.